Pengaruh Budaya Organisasi dan Komitmen Karyawan Terhadap Kinerja Pegawai di PT Lingkar Sakti Mas Banjarmasin - Kurniawan, Muhammad Aldo; Mardah, Siti; Amelia, Citra (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
This study aims to analyze the influence of Organizational Culture and Employee Commitment on Employee Performance at PT Lingkar Sakti Mas Banjarmasin. The research employs a quantitative approach with 32 respondents, all of whom were selected using a saturated sampling technique. The data collection instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression. The results show that the Organizational Culture variable (X1) has a significant effect on Employee Performance (Y), with a t value of 5.475 > t table 2.042 and a significance level of 0.000 < 0.05. In contrast, the Employee Commitment variable (X2) does not significantly affect Employee Performance, with a t value of 1.731 < t table 2.042 and a significance level of 0.094 > 0.05. The simultaneous test (F test) indicates that Organizational Culture and Employee Commitment jointly have a significant effect on Employee Performance, as shown by an F value of 19.710 > F table 3.328 and a significance level of 0.000 < 0.05. In conclusion, improving employee performance can be achieved through the implementation of a strong organizational culture supported by consistent and balanced employee commitment.